2017
DOI: 10.1186/s41182-017-0078-1
|View full text |Cite
|
Sign up to set email alerts
|

The importance of human population characteristics in modeling Aedes aegypti distributions and assessing risk of mosquito-borne infectious diseases

Abstract: Background: The mosquito Aedes aegypti has long been a vector for human illness in the Southeastern United States. In the past, it has been responsible for outbreaks of dengue, chikungunya, and yellow fever and, very recently, the Zika virus that has been introduced to the region. Multiple studies have modeled the geographic distribution of Ae. aegypti as a function of climate factors; however, this ignores the importance of humans to the anthropophilic biter. Furthermore, Ae. aegypti thrives in areas where hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Alternatively, another study identified human population as a key factor to shape the ecological niche of at least Ae . aegypti [57]. The inclusion of these factors to the model will allow better predictions; however, lack of parallel future data remains a gap in knowledge, particularly when we project these models to the future.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, another study identified human population as a key factor to shape the ecological niche of at least Ae . aegypti [57]. The inclusion of these factors to the model will allow better predictions; however, lack of parallel future data remains a gap in knowledge, particularly when we project these models to the future.…”
Section: Discussionmentioning
confidence: 99%
“…Biotic and abiotic variables are expected to shape the biogeographic constraints and opportunities of infectious agents distribution. Those variables are widely used in niche modelling of vectors [ 12 , 59 , 60 ], and anthropogenic variables are much less used [ 61 ]. Movement variables summarise the limitation and the accessibility, possible barriers, or spreading opportunities, but are far less considered in disease biogeography [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti abundance may be associated with population density [64]. Proximity to highways in our study was not necessarily suggestive of greater human population density, which may have greater influence on mosquito abundance [65, 66]. These results may suggest that the immediate household environment contributes more to larvae and pupae abundance than more distant neighborhood factors [6769].…”
Section: Discussionmentioning
confidence: 87%